Congruence between teachers’ and parents’ role construction and expectations about their involvement in homework - Deslandes, Rollande; Rousseau, Nadia (International Journal about Parents in Education, 2023)
This study explores individual, family and student factors in relation to parents’ and teachers’ role construction and mutual expectations regarding homework. Survey data were collected in spring 2005 from parents and teachers at both the elementary and the secondary levels. Parents’ positive attitudes toward homework are associated with more perceived responsibilities on their part. Contrary to parents at the secondary level, parents of elementary students with learning difficulties, as compared to parents of students who succeed well, do not believe as much that “checking homework and making sure that it is done” is part of their parental role. There is no difference among teachers regarding the understanding of their role in homework, regardless of attitude and work experience. At both the primary and secondary levels, teachers have higher expectations of the parents’ role in homework than parents do. Obviously, more work needs to be done related to the activities parents think that they are responsible for with respect to homework. Relative incongruence between parents’ role construction in homework and teachers’ expectations about their role should not be overlooked if we are to promote more positive family-school relationships.This research was supported by a grant from the Social Sciences and Humanities Research Council of Canada (SSHRC). The two authors are regular researchers at the Centre de Recherche et d’Intervention sur la Réussite Scolaire (CRIRES).